ONLINE BUSINESS STRATEGY ANALYSIS THROUGH TIKTOK SHOP DIGITAL NETWORK PLATFORM MARKETPLACE - Asrindah Nst; Aldi Fasta Bhiqul Khairat (Universitas Dharmawangsa Medan, 2023)
ABSTRACT Digital marketing also facilitates communication between producers, marketers and consumers or buyers in sales activities. The phenomenon of online shopping has become something that continues to be discussed to this day. One of the app providers of online shopping features is stickers. TikTok has an interesting feature that the business shop can benefit from the use of tikTok. The research discusses how online sales can be applied on touch platforms, knowing strategies and knowing promotions that can be used. The research uses a qualitative method with a phenomenological research design to analyze the meaning of the social media platform TikTok as an online business marketing strategy. TikTok has interesting features and a comprehensive database. In addition to the increasing popularity of TikTok applications, there is a possibility that can benefit from the use of tikTok. TikTok’s objectives in the corporate world are shifting from entertainment media platforms to tools for business strategy. Tiktok has many advantages and promotional features that are very profitable to sellers and consumers, such as affiliate tags and some profitable strategies that can facilitate promotions such as trend hashtags and view ads.Keywords: Affiliation, Market Place, Tiktok Shop